CALPHAD-aided design for superior thermal stability and mechanical behavior in a TiZrHfNb refractory high-entropy alloy. (1st March 2023) - Li, Tianxin; Wang, Shudao; Fan, Wenxue; Lu, Yiping; Wang, Tongmin; Li, Tingju; Liaw, Peter K.
Abstract: TiZrHfNbTa refractory high-entropy alloys (RHEAs) are now at the research frontier of advanced metallic materials due to their exceptional mechanical performance, particularly at high temperatures. However, the TiZrHfNbTa RHEAs exhibit poor phase stability at intermediate temperatures (600 – 1, 000 °C). The present study aimed to tailor their phase stability and mechanical properties via the calculation of phase diagrams (CALPHAD) approach. We found that Ta and Hf were detrimental to the phase stability of the TiZrHfNbTa RHEAs. Accordingly, a Ta-free and Hf-depleted Ti30 Zr30 Hf16 Nb24 RHEA with outstanding phase stability was designed, which could remain a single-phase body-centered cubic (BCC) structure after annealing at 600 °C for 200 h. Furthermore, numerous (Ti, Zr)-rich nano-precipitates were dispersedly formed in the cold-rolled plus recrystallization-annealed (CR+A) Ti30 Zr30 Hf16 Nb24 RHEA. The nano-precipitates controlled by the spinodal decomposition mechanism had an identical BCC lattice. The lattice fringes with ( 1 1 ¯ 0 ) Miller indices bent from the matrix phase to the nano-precipitates, causing a strong local strain field near the phase boundaries. The CR+A alloy possessed a yield strength of ∼ 800 MPa and tensile fracture elongation of ∼ 34.0%, showing a superior strength-ductility combination. The strain measurement by a digital image correlation indicated that the CR+A alloy exhibited a more substantial plastic stability than the as-cast alloy. Detailed observations of deformation microstructures through a transmission electron microscope and electron back-scattered diffraction revealed the origin of strength and ductility. Dislocation cross-slip and kink bands tended to form in the CR+A alloy during deformation and were capable of accommodating dislocation slip against stress concentration. Labusch's model uncovered that solid-solution strengthening contributed the most to yield strength. The present study provides a paradigm for the superior thermostability and controllable nanophase-precipitation behavior in RHEAs. Graphical abstract: Image, graphical abstract